Study guides

☆☆

Q: 6x plus 3 8x plus 14?

Write your answer...

Submit

Related questions

6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.

2x + 15 = 8x + 43 -6x = 28 x = -6 / 28 = -3 / 14

-6x-17 ≥ 8x+25Add 17 to both sides:-6x ≥ 8x+42Subtract 8x from both sides:-14x ≥ 42Divide both sides by -14. Since we are diving by a negative number, flip the sign.x ≤ -3

8x-3+6x-1 = 12x+614x-4 = 12x+614x-12x = 6+42x = 10x = 5

Multiplying out the brackets it then is: 6x+8x+8-3 = 14x+5 when simplified

6x+1-x-3 = 8x-5-8 5x-2 = 8x-13 5x-8x = -13+2 -3x = -11 x = 11/3

(4x - 3)(2x + 3)

8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)

74

-14x -14 + 6x= 2.7 1) Combine the like terms; -14x + 6x. Which leaves you with: -8x -14=2.7 2) Add the -14 to the 2.7 -8x=16.7 3) The divide; x/8 and 16.7/8 Which leaves you with: x= 2.0875

8x^3 - 12x^2 + 6x - 9 = (8x^3 - 12x^2) + (6x - 9) = 4x^2(2x - 3) + 3(2x - 3) = (4x^2 + 3)(2x - 3)

8x2 + 6x - 9 = 8x2 + 12x - 6x - 9 = 4x(2x + 3) - 3(2x + 3) = (2x + 3)(4x - 3)

-15x - 3

72xx

5

2(x + 3)(x^2 + 4)

3x+50=6x+14 50-14=6x-3x 36=3x x=36 / 3 therefore x=12

0. 6x + 3 = 5x + 141. 6x = 5x + 11 [subtracting 3]2. x = 11 [subtracting 5x]

8x + 6 = 2x + 24 To solve, collect like terms on each side; collect the x's on the left, the numbers on the right: 8X + 6 = 2x + 24 8x - 2x = 24 - 6 6x = 18 6x / 6 = 18 / 6 x = 3

This is how I did it:8x3+4x2+6x+3[8x3+4x2]+[6x+3][(4x2)(2x+1)]+[(3)(2x+1)]....as you can see, this is in the general form of ab+cb, which factored is b(a+c), so:(2x+1)(4x2+3)

hcf(6x², 8x) = 2x 6x² = 2 × 3 × x² 8x = 2³ × x → hcf = 2 × x = 2x

AC is in the range (2x - 10, 14x + 4)

x=-3

-6x - 17 >= 8x + 25 -17 >= 14x + 25 -42 >= 14x -3 >= x Therefore x is less than or equal to -3.

4x2 + 6x - 3 (with no remainder)